Finding Strength Through Adversity: An Exploratory Study of the Role of Homesickness among International Students - Wang, Lei; Mafa, Mpoi (Asian Social Work Journal, 2024)
Homesickness is a well-studied phenomenon among international students, traditionally viewed as a negative experience. However, emerging research suggests that it can also have positive implications for other individuals. This exploratory study aims to address this gap by investigating the potential benefits of homesickness on international students from diverse cultural backgrounds and exploring the coping mechanisms they employ to manage it. Utilizing a purposive sampling approach, the study recruited ten participants: five from Africa, three from America, and two from Asia. Semi-structured interviews were conducted with each participant, allowing for a comprehensive exploration of their experiences with homesickness, its impact on their lives, and the coping strategies they utilized. The findings indicate that homesickness can act as a catalyst for positive change, fostering identity-based cohesion, a willingness to learn, and cultural appreciation resilience. Participants reported re-evaluating and redefining their existing relationships, underscoring the significance of social connections. The study also identified various coping mechanisms employed by students, including cultural engagement, social networks, and the utilization of emotional coping strategies. Overall, our study suggests that while homesickness presents challenges, it can also serve as a trigger for personal growth and positive development among international students.